Chapter Fashion, emulation and social classes in late medieval Valencia. Exploring textile consumption through probate inventories - Garcia Marsilla, Juan Vicente (Datini Studies in Economic History, 2022)
Abstract: This article explores the personal garments present in the probate inventories of 83 individuals that lived in the city of Valencia and its hinterland during the long fourteenth century. The paper explores the differences between both groups of individuals, the urban and the rural one, in aspects such as the typologies of the pieces of clothing, the colours, finishes, complements and fabrics employed in their design. It also tracks the spread of particular pieces of clothing across both groups of deceased before and after the Black Death, and discusses how far these changes were guided by emulative motivations.